Ultrasound-guided continuous thoracic paravertebral block alleviates postoperative delirium in elderly patients undergoing esophagectomy: A randomized controlled trial. Issue 17 (April 2020) - Jin, Liang; Yao, Rui; Heng, Lei; Pang, Bo; Sun, Fu-Guo; Shen, Ying; Zhong, Jun-Feng; Zhao, Pan-Pan; Wu, Cong-You; Li, Bei-Ping
Abstract: Background: Delirium is a common postoperative complication in older patients undergoing thoracic surgery and presages poor outcomes. Postoperative pain is an important factor in the progression of delirium. The purpose of this study was to test whether continuous thoracic paravertebral block (PVB), a more effective approach for analgesia, could decrease the incidence of delirium in elderly patients undergoing esophagectomy. Methods: A total of 180 geriatric patients undergoing esophagectomy were randomly divided into 2 groups and treated with PVB or patient-controlled analgesia (PCA). Perioperative plasma CRP, IL-1β, IL-6, and TNF-α levels were detected in all patients. Pain intensity was measured by a numerical rating scale. Delirium was assessed using the confusion assessment method. Results: The incidence of postoperative delirium was significantly lower in the PVB group than in the PCA group. Patients in the PVB group had lower plasma CRP, IL-1β, IL-6, and TNF-α levels and less pain when coughing after surgery. Conclusions: Ultrasound-guided continuous thoracic paravertebral block improved analgesia, reduced the inflammatory reaction and decreased the occurrence of delirium after surgery. Abstract : Supplemental Digital Content is available in the text